UJI AKTIVITAS ANTIINFLAMASI EKSTRAK ETANOL KULIT BAWANG MERAH (Allium ascalonicum L.) TERHADAP LUKA BAKAR PADA MENCIT JANTAN (Mus musculus L.) - Hulwatul Badriyah; Sari Defi Okzelia; Iin Ruliana Rohenti (Nusantara Hasana Berdikari, 2022)
Shallots (Allium ascalonicum L.) is one type of tuber that is widely used as spice in cooking by the community. However, many people do not know that shallot peel which is considered as waste has many benefits and contains secondary metabolites that possess antibacterial, antidiabetic, antiinflammation and antioxidant activities. This study aimed to determine antiinflammation activity of ethanol extract of shallot (Allium ascalonicum L.) peel against burn in male rats (Mus musculus L.). Shallot peel simplicia was macerated using 96% ethanol solvent then conducted phytochemical screening, tested for water content and pH. Antiinflammation activity was observed with various extract concentrations of 10%, 20% and 30%. Burns X ointment was used as a positive control and petroleum jelly was used as a negative control. This study consisted of 5 groups of rats, each group consisting of 5 rats with each treatment. Tested animals were first adapted to their environment and made burns using metal of 20.00 mm. Based on the results of the study, it was found that the ethanol extract of the shallot peel contained flavonoids, tannins, alkaloids and terpenoids. The water content obtained in the extract was 11.73% with pH value of 4.70. The best antiinflammation activity on the shallot peel in healing burns was at concentration of 30% with healing percentage of 64.25%. The healing percentage at concentration of 10% and 20% were 53.75% and 59.20% respectively. Ethanol extract of shallot peel (Allium ascalonicum L.) was potential as antiinflammation agent against burn in male rats.